Aspects of ECMWF model performance in polar areas. (11th November 2014) - Bauer, P.; Magnusson, L.; Thépaut, Jean‐Noël; Hamill, Thomas M.
Abstract : Global numerical weather prediction skill over polar areas is assessed, mostly based on the European Centre for Medium‐Range Weather Forecasts (ECMWF) system but also the Met Office, Japan Meteorological Agency (JMA), Environment Canada and National Centers for Environmental Prediction (NCEP) analysis data. Polar forecast verification against analyses shows a similar trend of forecast improvement over the past 12 years compared with improvements at lower latitudes. These improvements are presumably due to increased model resolution and model sophistication, improved data assimilation methods and increased observational data coverage and better data quality. By comparing ECMWF's real‐time forecast skill changes against those from reforecasts initialized from reanalyses, it is possible to quantify how much of the improvement is from system improvements and how much is attributable to weather variability. Ensemble skill also improved over time and, again, consistently across latitudes. The quality of analyses serving for forecast verification and initialization has been investigated further. An intercomparison of The Observing system Research and Predictability Experiment (THORPEX) Interactive Grand Global Ensemble (TIGGE) analyses and forecasts revealed substantial differences for surface parameters, but also at lower levels in the troposphere, where most of the physical processes relevant to weather in the short‐to‐medium range take place over the poles. The differences between the TIGGE analyses were generally much larger than differences between members of the ECMWF 4D‐Var ensemble of analyses generated internally at ECMWF. This suggests that neither the multi‐analysis approach nor ensemble data assimilation may represent polar analysis uncertainty properly. This is particularly visible at the surface and lower levels in the atmosphere. Forecast spread and error match much better north of 65∘N where less atmospheric variability prevails along the entire forecast range, while in areas of significant synoptic activity the spread also appears too low.